(untitled) (Research, Society and Development, 2021)
The aim of this study is to evaluate the prevalence and factors associated with TMD in students who completed the Physiotherapy course. This is a cross-sectional study, carried out with students from the eighth to the tenth period, through the application of questionnaires, aiming to identify the sociodemographic and academic profile, parafunctional habits, severity of TMD and the level of anxiety. The data were analyzed using the Statistical Package for the Social Sciences program The Linear Trend Test was applied and a significant value of p <0.05 was considered. The data were expressed in tables. Thirty students were evaluated. The prevalence of TMD was 100.0%, with a higher incidence of severity (66.7%, n=20, p=0.001) and moderate anxiety (46.6%, n=14), with greater involvement in females (76.6%, n=23, p=0.039), showing symptoms of headache (70%, n=21), crackling (65.7, n=17) and cervical tension (93.3, n = 28). The prevalence of TMD and anxiety is high in students completing physiotherapy, manifesting itself with moderate severity and being more affected by female students.